2016
DOI: 10.1080/2000656x.2016.1178651
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of the cheek advancement flap, a report of 41 cases

Abstract: The cheek advancement flap is a suitable technique for reconstruction of large cheek skin defects after excision of skin malignancies. However, patients should be informed that long-term complications, including ectropion, can occur. Additional follow-up might lead to an early detection of these late effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As another complication, this surgery may cause blood flow disturbances in the skin around the auricle and the ear lobe. [10][11][12] Lim et al 13 reported that the incidence of complications in cervicofacial flap surgery was 7.1%. Additionally, desensitization of the earlobe may occur in cases where the great auricular nerve is damaged when the posterior ear is incised.…”
Section: Discussionmentioning
confidence: 99%
“…As another complication, this surgery may cause blood flow disturbances in the skin around the auricle and the ear lobe. [10][11][12] Lim et al 13 reported that the incidence of complications in cervicofacial flap surgery was 7.1%. Additionally, desensitization of the earlobe may occur in cases where the great auricular nerve is damaged when the posterior ear is incised.…”
Section: Discussionmentioning
confidence: 99%
“…The former depends on the rich subdermal plexus of vessels, and the later relies upon more reliable large perforator branches from facial and transverse facial arteries [12]. Commonly encountered complications with these flaps are distal flap edge necrosis, lower eyelid ectropion, and hematoma [13, 14]. The deep plane technique has reduced the rate of these postop sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned options, the nasal sidewall/cheek portion could be managed most simply by cheek advancement or rotation, lax cheek skin being an excellent reservoir for defects involving the medial cheek or nasal sidewall. 2 Thus, a cheek advancement flap was used for the closure of the inferior aspect of the defect, leaving only the deep medial canthal and upper nasal wounds remaining (Figure 2).…”
Section: Considerationsmentioning
confidence: 99%